1976
DOI: 10.1128/jb.126.2.1002-1004.1976
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ammonium Ions on the Induction of Nitrite Reductase inNeurospora crassa

Abstract: Results with strain am-la, a glutamate dehydrogenaseless mutant, showed that ammonium ions must first be metabolized in order to repress nitrite reductase in Neurospora.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1978
1978
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Used in a study showing glutamine to have a role as corepressor of uricase synthesis (1118). Used to study nitrogen assimilation and metabolism (503) and nitrogen metabolite repression (186,291). Efficient procedure for selecting new am mutants (551).…”
Section: Alx-1mentioning
confidence: 99%
See 1 more Smart Citation
“…Used in a study showing glutamine to have a role as corepressor of uricase synthesis (1118). Used to study nitrogen assimilation and metabolism (503) and nitrogen metabolite repression (186,291). Efficient procedure for selecting new am mutants (551).…”
Section: Alx-1mentioning
confidence: 99%
“…Lacks nitrite reductase (185) (Fig. 19), which is subject to positive nitrogen metabolite repression (186). Affected by nit-2 and MS5 regulator genes (838, 1076a) (see nmr-1).…”
Section: Pb) (94)mentioning
confidence: 99%
“…Dantzig et al (6) found that in a N. crassa mutant lacking NADP-glutamate dehydrogenase, ammonium was unable to repress the formation of nitrate reductase, although certain amino acids could still repress the enzyme. This observation led the authors to suggest that ammonium repression was, in fact, mediated by a nitrogen metabolite(s) other than ammonium ions, an idea that is not new (3,5,8). Studies in our laboratory with a glutamine auxotroph of N. crassa, identified glutamine (or a close metabolite of glutamine) as a corepressor of nitrate reductase (19).…”
mentioning
confidence: 99%